Enhancing Traveler Experiences: Time Management And Transfer In-Out Services Innovation - Nurhaliyani Nurhaliyani; Nurul Aini; Istiqomah Fi Ihsani (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This study aims to improve the service and time management of a tour guide for travelers or clients. This study was analyzed using a descriptive-qualitative design. This study were used theories from several journals to collect the data. Findings show that the ways to enhance travel experiences are: 1.) The strategies for time management; 2.) The strategies for transfer in-service innovation; 3.) The challenges for transfer services.